My Bad, You Got This: witnessing, therapist attitude and the synergy between psychedelics and inner healing intelligence in the treatment of trauma - Fischman, Lawrence (Frontiers in Psychology, 2025)
The MAPS (Multidisciplinary Association for Psychedelic Studies) sponsored MDMA-assisted therapy protocol has had greater success in treating trauma in preliminary clinical trials than any prior psychotherapeutic, pharmacologic, or combined approach. It is predicated on a synergy between drug action and the participant’s inner healing intelligence. The latter is described mainly by analogy with the body’s capacity to heal itself, and the treatment is characterized as a means of activating or accessing this capacity. How is this rather mysterious-sounding process so effective? I suggest that the therapist’s full commitment to, and trust in this treatment framework, along with the medication’s subjective enhancement of trust, encourages individuals who have suffered trauma and have difficulty trusting others to engage the therapist as a kind of witness. I discuss parallels between the therapeutic attitude implied in the inner healing intelligence model and the way a therapist can act as witness in the resolution of dissociative enactment in relational psychoanalysis. Trusting the healing capacity of one’s inner healing intelligence is dynamically equivalent to trusting the relational process. This makes trusting one’s inner healing intelligence a process of feeling witnessed. In both settings, the therapist’s willingness to acknowledge her technical limitations or failings, coupled with a conviction that the participant/patient’s primary need in processing trauma is to feel witnessed, facilitates the integration of dissociated experience.